Designing an Electronic Traffic Light System - Luz Luz, David A.; Mendigaña Figueredo, Jhon E. (Ingeniería Solidaria, 2014)
Abstract. This article is the product of the degree project titled “Design of an electronic traffic light system developed in the Gaseosas Colombianas del Sur company” and was presented and defended in 2010 in the Technology Faculty of the Universidad Distrital Francisco Jose de Caldas. The system consists of two TrafiCam® sensors (vehicle presence sensors), based on video detection technology tested worldwide. It uses a CMOS camera (black and white) and an RS485 or usb communication interface, together with a control system programmed and designed with PSoC (Programmable System on Chip) microcontrollers that adjusts to the needs of the TrafiCams and the requirements for adequate vehicle and pedestrian flow within the company grounds. The most important finding of this research study is that the cameras in the system designed can detect objects (vehicles) that enter the virtual loop, at rest and in movement, in real time.
Keywords: PSoC; RS485; traffic lights; TrafiCam®